"Enticing case study" or "celebrated anomaly"? Policy learning from the Cuban health system. (6th September 2017) - Baggott, Rob; Lambie, George
Summary: Cuba is regarded as having achieved very good health outcomes for its level of economic development. It has adopted policies and programs that focus on prevention, universal access to healthcare, a strong primary care system, the integration of health in all policies, and public participation in health. It has also established a strong and accessible system of medical education and provides substantial medical aid and support to other countries. Why then, it may be asked, has the Cuban experience not had greater influence on health policies and reforms elsewhere? This article, based on a literature review and new primary sources, analyzes various factors highlighted in the policy transfer literature to explain this. It also notes other factors that have created greater awareness of Cuban health achievements in some countries and which provide a basis for learning lessons from its policies.